2006
DOI: 10.1590/s1806-83242006000300005
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of pixel values for two photostimulable phosphor plates in consecutive standardized scannings

Abstract: ABSTRACT:The objective of the present study was to determine the reproducibility of the pixel values obtained with the Digora system (Soredex, Finland). Exposures were standardized, with variation in exposure and scanning time of two photostimulable phosphor plates containing a stepwedge image. The smallest variation in pixel values ranged from 50 to 75%, with the widest variations being observed in less dense steps. A signifi cant difference in pixel values was observed in terms of X-ray exposure and scanning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 18 publications
1
8
1
1
Order By: Relevance
“…Thus, when an X-ray beam penetrates an analyzed region, the presence of soft and hard tissues in this trajectory influences the gray values. In this study, the highest gray values were observed in the most radiopaque regions (AB and S3), and the lowest values were observed in the most radiolucent regions (ST and S1) 5,8,16,17 (Table 1).…”
Section: Discussionmentioning
confidence: 52%
See 4 more Smart Citations
“…Thus, when an X-ray beam penetrates an analyzed region, the presence of soft and hard tissues in this trajectory influences the gray values. In this study, the highest gray values were observed in the most radiopaque regions (AB and S3), and the lowest values were observed in the most radiolucent regions (ST and S1) 5,8,16,17 (Table 1).…”
Section: Discussionmentioning
confidence: 52%
“…5 According to Pietrobelli et al 18 attenuation occurs when the photon signal crosses an element, chemical component or solution, spontaneously reducing the intensity through atomic interactions and leading to the absorption and dissipation of photons. Thus, when an X-ray beam penetrates an analyzed region, the presence of soft and hard tissues in this trajectory influences the gray values.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations